2018
DOI: 10.1007/s10549-018-4774-2
|View full text |Cite
|
Sign up to set email alerts
|

Personal and clinical social support and adherence to adjuvant endocrine therapy among hormone receptor-positive breast cancer patients in an integrated health care system

Abstract: Women with low personal or clinical social support had higher AET non-adherence. Clinician teams may need to fill support gaps that compromise treatment adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 28 publications
2
37
0
Order By: Relevance
“…In-depth, time consuming and person-centered conversations about AET often occurred to ensure women understood the benefits and risks of AET, while also respecting their values and beliefs. These findings are consistent with previous research that also found women's satisfaction with clinical support [22], the quality of the patient-physician relationship [23], frequent, patient-centered communication [24,25], preparedness for the possibility of side effects and physician involvement in decisionmaking [23] were significantly correlated with greater AET adherence.…”
Section: Discussionsupporting
confidence: 92%
“…In-depth, time consuming and person-centered conversations about AET often occurred to ensure women understood the benefits and risks of AET, while also respecting their values and beliefs. These findings are consistent with previous research that also found women's satisfaction with clinical support [22], the quality of the patient-physician relationship [23], frequent, patient-centered communication [24,25], preparedness for the possibility of side effects and physician involvement in decisionmaking [23] were significantly correlated with greater AET adherence.…”
Section: Discussionsupporting
confidence: 92%
“…A total of 26 studies examined healthcare provider (HCP)-related factors for association with adherence (see Table 6 ) [ 25 , 29 , 31 , 32 , 41 , 44 , 45 , 49 , 50 , 51 , 56 , 60 , 62 , 65 , 67 , 70 , 71 , 72 , 73 , 75 , 79 , 81 , 84 , 85 , 86 , 87 ]. Quality of relationship with HCP was most consistently associated in univariate models (83% of the time) but less so (50% of the time) in multivariate models.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies [ 25 , 31 , 34 , 41 , 52 , 56 , 65 , 73 , 74 , 77 , 79 , 80 , 84 , 86 , 88 ] examined sociocultural factors (see Table 7 ). Social support was examined 13 times, associated with adherence most of the time (78%) in univariate models and over half the time in multivariate models.…”
Section: Resultsmentioning
confidence: 99%
“…37 Very few studies have focused on the role of patients' supportive networks in adherence to adjuvant ET. In a recent study from a large Californian cohort, Kroenke et al 38 showed a higher risk of nonadherence with low social or clinical support. In the French cohort, Huiart et al 31 found a higher risk of early discontinuation of ET in YW with the lowest social support.…”
Section: Discussionmentioning
confidence: 98%